HUBUNGAN ANTARA PENYESUAIAN SOSIAL DAN KEMAMPUAN MENYELESAIKAN MASALAH DENGAN KECENDERUNGAN PERILAKU DELINKUEN PADA REMAJA - Setianingsih, Eko; Uyun, Zahrotul; Zuwono, Susatyo (Faculty of Psychology, Diponegoro University, 2006)
The purpose of this research is to know the correlation between socialadjustment and problem solving with the behavioral delinquency at adolescent. Bycluster random sampling, subjects are 78 students of SMU PGRI 01 Kendal. Themeasurement tools are behavioral of delinquency scale, social adjustment scale andproblem solving scale. Results shows that there are very significant correlationbetween social adjustment and problem solving with the behavioral delinquency.Key words : behavioral delinquency at adolescent, social adjustment, problem solving